Análisis para la aplicación de los clasificadores en el aprendizaje automático. - Peñafiel Benítez, Narcisa Janeth (2022)
This document is a case study that is oriented with the research subline of the systems engineer career, and the subline is data and telecommunications processes”, its objective is the analysis of the application of machine learning classifiers and the way in which they contribute to science and technology. It is a document clearly related to the study of artificial intelligence and its classification algorithms, and recommends some forms of application that can be deployed and the nature and set of data available for its application. Here, the different existing machine learning methods that are related to classification are analyzed, from the techniques that serve as a basis to the most recent models, with the purpose of finding the best model that makes it possible to know the polarity of an indication. Likewise, it is important to indicate that importance has been given to the participation of systems engineering professionals, who are aware of these aspects related to Artificial Intelligence Machine Learning, to whom an interview has been sent with instruments such as formulations 4 questions extended so that with your opinion this case study is further strengthened with the author's analysis.